8y+7=4y-29

Simple and best practice solution for 8y+7=4y-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8y+7=4y-29 equation:


Simplifying
8y + 7 = 4y + -29

Reorder the terms:
7 + 8y = 4y + -29

Reorder the terms:
7 + 8y = -29 + 4y

Solving
7 + 8y = -29 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
7 + 8y + -4y = -29 + 4y + -4y

Combine like terms: 8y + -4y = 4y
7 + 4y = -29 + 4y + -4y

Combine like terms: 4y + -4y = 0
7 + 4y = -29 + 0
7 + 4y = -29

Add '-7' to each side of the equation.
7 + -7 + 4y = -29 + -7

Combine like terms: 7 + -7 = 0
0 + 4y = -29 + -7
4y = -29 + -7

Combine like terms: -29 + -7 = -36
4y = -36

Divide each side by '4'.
y = -9

Simplifying
y = -9

See similar equations:

| 9(4-2x)=3(2-6x) | | 15x^2-50x=0 | | 5x-4x=-6+3 | | 0.60x+0.30(70)=0.30(148) | | h/3+h/6=1 | | 7y-20=-2y-47 | | 9=-4.3 | | -6+6n=6(10-10n) | | 3m+8=m+18 | | 36p+4j=33 | | 3x^4+21x^3-36x^2+3=0 | | 2g+4h=47 | | 2g*4h=47 | | 3y-11=5y-35 | | 4b=9(b+5) | | -6y+17=-9y-7 | | 7b-10+1+10b=60 | | -3k+14=-4+3k | | 3X^2-3X+10=04 | | 1.6y+3.2=-1.6 | | 3x^4+20x^3-36x^2+3=0 | | 6x^2+57x+90=0 | | M-2-7m+2=-18 | | -2.5x=.25 | | 2/5(25)-8=-1/5(25)+7 | | -9x+15=22-4(x+12) | | x^4+-5x^3+-3x^2=0 | | -2(-3m-8)+7m=94 | | 8x-8y=8 | | 7y-7-4y+6=0 | | y+15=-3y-9 | | qx+rx=s |

Equations solver categories